The tax impacts of the portfolio rebalance for Czech investors - Luňáček, Martin; Smrčka, Luboš; Žilák, Pavel; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2018)
Within the area of portfolio management, this thesis deals with the issue of automated portfolio rebalancing which has gained popularity recently – mainly due to the upswing of so-called robo advisors, which are using modern technologies to automate and streamline processes. The thesis focused on costs and benefits of rebalancing, special attention was paid to tax impacts of rebalancing. The results of the simulation of globally diversified portfolio rebalancing using various strategies on a historical market data from the years 2006-2017 mainly support the findings that rebalancing helps maintaining portfolio allocation while the positive impact on risk-return trade-off in real life environment is debatable. The tax costs of rebalancing are highly dependent on rebalancing frequency and market performance in a particular year. In the observed period, the rebalancing strategies with ten percent drift threshold and either weekly or monthly monitoring proved to generate the best results – they slightly increased risk-adjusted returns and resulted in only on average 3 yearly rebalancing events producing taxable amount worth about one percent of the total average portfolio value. Given various rebalancing strategies, the annual portfolio returns decreased by on average 0,2-0,6 % due to the tax costs related to rebalancing.
Vedoucí práce: Luboš Smrčka
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses